Ongoing Narrative Meaning-Making Within Events and Across the Life Span. (December 2017) - Fivush, Robyn; Booker, Jordan A.; Graci, Matthew E.
Individuals create meaning from the events in their lives, and the ways in which they do this has important implications for identity and well-being. We argue that this is a deeply developmental process. Narrative meaning-making consists of a set of developmentally acquired skills and abilities such that individuals are capable of different forms of meaning creation at different developmental periods. Further, narrative meaning-making emerges differentially across days, weeks, months, and years after an experience, and this event processing takes place within ongoing developmental change. Narrating life experiences both reflects and creates modes of meaning-making in a complex, reciprocal system.